Peculiarities of the endocrine status of women with precancerous lesions of the vulva - V. Dunaevskaya (Kazimierz Wielki University, 2024)
The purpose of the study was to determine the hormonal profile of peripheral blood in women with precancerous lesions of the vulva.Material and methods. 309 women with precancerous lesions of the vulva and 60 gynecologically healthy women aged 25 to 70 years were included in the study. Patients with precancerous lesions were divided into 4 groups depending on the nosological unit: 87 women with severe vulvar dysplasia dependent on HPV (VHSIL), 154 individuals with differentiated vulvar dysplasia independent of HPV (dVIN), 36 patients with extramammary Paget's disease of the vulva (VPD) grade Ia and 32 women with melanoma in situ of the skin vulva In the groups with VHSIL, with dVIN, with melanoma in situ, there were women of premenopausal and postmenopausal age, therefore, for the comparison of hormonal data in these groups, subgroups were selected according to age: subgroups with persons younger than 50 years, subgroups of women aged 50 years and older. 60 conditionally healthy women of the control group also included 30 people under 50 years and 30 people 50 years and older. The levels of estradiol (E2), progesterone (P4), free testosterone (Tf), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), anti-Müllerian hormone (AMH), insulin, thyroid-stimulating hormone (TSH), free triiodothyronine (T3f), free thyroxine (T4f), antibodies to thyroperoxidase (ATPO)in blood serumand HOMA indexwere determined. The results. There was no difference between serum LH and FSH levels in women with various precancerous diseases of the vulva under the age of 50 years. Individuals with dVIN were characterized by the highest level of PRL (24.44±1.55 ng/ml). Among women aged 50 years and older, the highest levels of LH, FSH and PRL were observed in persons with melanoma in situ - respectively 36.90±2.09 mIU/ml, 74.67±4.06 mIU/ml, 9.85±2.03 ng/ml; the level of FSH and PRL was higher, and the LH/FSH ratio was lower than in controls in all precancerous diseases of the vulva. No statistically significant difference was found between the basal levels of serum P4 and AMH in subgroups of women younger than 50 years and 50 years and older. Among both premenopausal and postmenopausal women, the highest average levels of E2 were recorded in women with melanoma in situ (104.61±10.22 pg/ml and 30.71±1.90 pg/ml), Tf and Tf index - in patients with dVIN (3.20±0.10 pg/ml and 1.58±0.05 pg/ml vs. 8.25±0.24% and 3.77±0.10%, respectively). Features of the thyroid status were the highest indicators of TSH and ATP in persons with dVIN both in premenopause (2.68±0.30 mIU/ml and 196.39±76.48 IU/ml) and in postmenopause (2.23±0 .09 mIU/ml and 123.46±16.07 IU/ml). The average level of 25(OH)D did not differ statistically significantly between women with various precancerous diseases of the vulva. The level of insulin and NOMA index among premenopausal women was the highest in women with melanoma in situ (14.33±1.55 mIU/ml), in postmenopausal women with VPD (14.90±1.02 mIU/ml), HOMA index - respectively, with dVIN (2.87±0.30) and with VPD (3.60±0.27). Insulin resistance was most common in premenopause among individuals with dVIN (53.33%), and in postmenopause - with VPD (72.22%).Conclusions. Features of the hormonal profile of people with precancerous diseases of the vulva under the age of 50 are the highest levels of PRL, TSH and ATPO in women with dVIN, the highest average levels of Tf and Tf index, insulin level and HOMA index - in patients with VPD, the highest average levels of E2- in women with melanoma in situ. Among postmenopausal patients, the highest levels of TSH and ATPO in women with dVIN, the highest average levels of Tf and Tf index, the level of insulin and NOMA index in patients with VPD, the highest average levels of LH, FSH, PRL and E2 in women with melanoma are characteristic features situ. The average level of 25(OH)D does not differ statistically significantly between women with various precancerous diseases of the vulva. Insulin resistance is most common in premenopausal individuals with dVIN, and in postmenopausal individuals with VPD.